The Effects of Inquiry-Based and Contextual Learning Strategies on English Writing Skills: A Prisma Systematic Review (2015–2025) - Sapto Sugiharto; Merry Lapasau; Widodo Widodo; Syahfitri Purnama; Bambang Sumadyo (JOLLT Journal of Languages and Language Teaching, 2026)
English writing proficiency among EFL learners in Indonesia remains below regional benchmarks, and despite growing interest in learner-centered pedagogies, there is limited synthesis comparing the effects of inquiry-based learning (IBL) and contextual teaching and learning (CTL), particularly regarding their combined impact. This study addresses this gap through a PRISMA-guided systematic literature review of empirical studies published between 2015 and 2025. Searches were conducted across major databases, including Scopus, Web of Science, ScienceDirect, and Taylor & Francis, yielding 35 eligible studies for analysis. A narrative synthesis complemented by a quantitative summary of comparable studies indicates that both IBL and CTL produce significant positive effects on students’ English writing performance, with a pooled effect size of approximately d ≈ 0.81 (95% CI [0.65, 0.97]), suggesting a moderate-to-large overall impact. IBL consistently enhances cognitive dimensions of writing, such as idea generation, organization, and critical thinking, whereas CTL demonstrates strong effects on engagement, contextual understanding, and learner motivation. However, direct comparative and hybrid studies remain limited, although preliminary evidence suggests additive benefits when both approaches are integrated. These findings imply that EFL teachers and curriculum designers should consider combining inquiry cycles with context-based writing tasks to simultaneously develop cognitive and affective dimensions of writing. Future research should prioritize rigorous comparative and longitudinal designs to validate the effectiveness of integrated IBL–CTL models across diverse EFL contexts.